Effects of a Chinese Patent Medicine Gushen’antai Pills on Ongoing Pregnancy Rate of Hormone Therapy FET Cycles: A Multi-Center, Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Cao, Xian-ling; Song, Jing-yan; Zhang, Xing-xing; Chen, Yan-hua; Teng, Yi-li; Liu, Hai-ping; Deng, Tai-you; Sun, Zhen-gao (Frontiers in Endocrinology, 2020)
In the past decade, the number of frozen-thawed embryo transfer (FET) has increased dramatically with the expansion of surgical indications and the improvement of freezing related technologies. How to improve the success rate and reduce the adverse effects of FET is our research priorities. This study aimed to investigate the safety and effectiveness of Gushen’antai pills（GSATP）by measuring the ongoing pregnancy rate (OPR) in patients of FET and hormone therapy（HT）cycle. From November 2019 to May 2020, 5 Chinese hospitals conducted a multi-center, randomized, double-blind, placebo-controlled study. In total, 271 HT cycle FET patients were randomized (1:1 ratio) to receive GSATP (6g, tid) or placebo (6g, tid) for 12 weeks of pregnancy. Patients, clinicians, and researchers were blinded to treatment allocation. The primary endpoint was the OPR at week 12 of pregnancy. The secondary endpoints were vaginal bleeding or brown discharge rate, implantation rate (IR), clinical pregnancy rate (CPR) and abortion rate (AR). Adverse events were recorded during the treatment period. The results showed that the OPR remained higher in the GSATP when compared to placebo (56.62% vs. 44.44%, p < 0.05). The vaginal bleeding or brown discharge rate was lower in the GSATP than the placebo group (10% vs. 23.08%, p < 0.05), while the IR (35.16% vs. 27.64%, p=0.07), CPR (58.82% vs. 48.15%, p=0.078) and AR (3.75% vs. 7.69%, p=0.504) were similar between GSATP and placebo groups. This multi-center, randomized, double-blinded, placebo-controlled clinical study showed that GSATP as a safe and effective treatment in HT cycle FET patients.